Rare retinal complications of bone marrow transplantation (BMT): a case report - Farhat Butt; Martin McKibbin (BMC Ophthalmology, 2018)
Abstract Background Bone marrow transplantation retinopathy is a rare condition affecting the posterior pole. The purpose of this case report is to highlight the possible risk factors and clinical features. Case presentation A 19y old male with relapsed and refractory acute lymphoblastic leukaemia was admitted under haematology with pyrexia of unknown origin. At the time of his admission, he reported bilateral and sequential visual impairment for 2 days. On examination, there was bilateral profound retinopathy across the posterior poles. This was symmetrical and with associated macular oedema. Infective aetiology was excluded and cyclosporine was stopped. Although no definitive treatment was initiated the visual acuity improved whilst macular oedema fluctuated. Conclusion BMT and chemotherapy can cause ocular complications but these are usually confined to the anterior segment. Posterior segment complications in the form of retinopathy is very rare. We report this case to highlight some of the clinical features and course of disease.